2022
DOI: 10.1007/s12471-022-01719-2
|View full text |Cite
|
Sign up to set email alerts
|

How is atrial fibrillation detected in everyday healthcare? Results of a Dutch cohort study

Abstract: Background Atrial fibrillation (AF) is a common arrhythmia with serious potential consequences when left untreated. For timely treatment, early detection is imperative. We explored how new AF is detected in patients aged ≥ 65 years in Dutch healthcare. Methods The study cohort consisted of 9526 patients from 49 Dutch general practices in the usual-care arm of the Detecting and Diagnosing Atrial Fibrillation study. We automatically extracted data from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…single-lead ECG) constituting the remaining 6% of cases. 16 A few other studies have assessed the chain of AF detection in such detail, but corroborating evidence on AF detection settings and the percentage of symptomatic patients can be found, e.g. in registry data on real-world patients with AF.…”
Section: Screening and Detection Of Atrial Fibrillation: Current Prac...mentioning
confidence: 81%
See 1 more Smart Citation
“…single-lead ECG) constituting the remaining 6% of cases. 16 A few other studies have assessed the chain of AF detection in such detail, but corroborating evidence on AF detection settings and the percentage of symptomatic patients can be found, e.g. in registry data on real-world patients with AF.…”
Section: Screening and Detection Of Atrial Fibrillation: Current Prac...mentioning
confidence: 81%
“…A thorough analysis of where and by whom AF is detected in routine practice was provided for the Dutch setting, in a post hoc analysis of the Detecting and Diagnosing AF (D 2 AF) trial with inclusion and follow-up in 2015–18. 16 , 17 This showed that the irregular heartbeat leading to an eventual AF diagnosis was observed in primary care in 55% of cases, with 60% of those leading to an AF diagnosis by GPs themselves. Of all newly diagnosed AF cases, one in three was detected by GPs, approximately half by cardiologists, and the remainder by other physicians.…”
Section: Screening and Detection Of Atrial Fibrillation: Current Prac...mentioning
confidence: 98%
“…study in Holland, in which symptoms triggered an examination for AF in 64.7% of patients subsequently diagnosed with AF in general practice, stroke was the trigger in 3.5%, and the diagnosis was incidental in 31.5%. 34 Therefore, including participants without symptoms identified AF among patients who might have been missed in everyday daily practice and were therefore not included in the study from Greenland describing AF prevalence based on diagnosis codes. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Symptoms are often the trigger for examining for AF [60], and the most described symptoms of AF are palpitations, lightheadedness/dizziness, shortness of breath on exertion, syncope and fainting, fatigue, dyspnea at rest, exercise intolerance and chest discomfort/pain [61,62]. However, as mentioned earlier, AF can be asymptomatic, and approximately 40-50% of patients do not report any symptoms [59,63,64].…”
Section: Diagnosing and Screening For Atrial Fibrillationmentioning
confidence: 99%
“…This difference may partly be attributed to undiagnosed AF in Greenland. Asymptomatic AF patients may remain unidentified unless actively screened, as subclinical AF is frequently diagnosed incidentally [60] and, emphasizing this point, one-third of the participants with previously undiagnosed AF in Study IV did not report any symptoms [4]. In addition, Holter recordings have only been available in Nuuk until recently, meaning that outside of Nuuk, there is a risk that paroxysmal AF may have been missed on the standard 12-lead ECGs used in the health care centers and stations, even among symptomatic patients.…”
Section: Prevalence Of Atrial Fibrillation In Greenlandmentioning
confidence: 99%